Team dynamics theory: Implications for the development of high-performing teams - Filho, E. (Advances in mental skills training, 2021)
High-performing sports teams are said to have "good chemistry," similar to how a complex molecule is formed by several chemical elements, and scholars and practitioners concur that success in team settings hinges on many well- connected team properties (Filho, 2015). To this extent, over the past 30 years, scholars and practitioners from various domains have tried to propose "best-fit models" that explain how myriad team processes are intertwined and influence team outcomes. In this chapter, Filho discusses a recent framework he proposed called team dynamics theory (TDT), which purports that cohesion (CO), team mental models (TMM), collective efficacy (CE), coordination (CD), and team outcomes are connected in a systemic fashion. In what follows, He discusses the theoretical roots, propositions, and applied implications of TDT. He concludes by outlining avenues of future research. In this chapter, he provides a brief overview of TDT, which purports that CO is the first team process to emerge because a group of individuals only becomes a team once they have set shared goals together. Furthermore, he suggestes that once CO is established, other key team processes influence one another, akin to the notion of reciprocal determinism in applied social psychology. Accordingly, practitioners should ensure that quality goals are set and that all correlates of cohesion are fostered in the early stages of team development. After that, practitioners should target multiple team processes simultaneously as, for instance, enhancing TMM influences CE and vice-versa. F. also suggests that practitioners should understand the subdimensions of CO, TMM, and CE if they are to develop high-performing teams so as to increase social and task bonds; shared and complementary mental models; and mastery experiences, effort, preparation, and persistence within a team. Overall, the goal of TDT is to help practitioners to develop systemic applied interventions to aid team development and functioning in sports and beyond, as well as to stimulate research toward the development of a general theory of team dynamics in sport, exercise, and performance psychology.